2004
DOI: 10.1038/sj.onc.1207347
|View full text |Cite
|
Sign up to set email alerts
|

Mutant α-actinin-4 promotes tumorigenicity and regulates cell motility of a human lung carcinoma

Abstract: The precise role of a-actinin-4 encoding gene (ACTN4) is not very well understood. It has been reported to elicit tumor suppressor activity and to regulate cellular motility. To further assess the function of human ACTN4, we studied a lung carcinoma cell line expressing a mutated aactinin-4, which is recognized as a tumor antigen by autologous CD8 þ cytotoxic T lymphocytes (CTL). Confocal immunofluorescence microscopy indicated that, while wild-type (WT) a-actinin-4 stains into actin cytoskeleton and cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 45 publications
3
33
0
2
Order By: Relevance
“…Furthermore, after extraction of the primary tumor the cytotoxic T lymphocyte clone targeting mutated α-actinin 4 persisted many years in the patient's blood (Echchakir et al, 2001). In the subsequent study, it has been shown that the above point mutation removes antiproliferative effect of ACTN4 protein in the cancer cell line and supports the notion that ACTN4 may be both tumor suppressor as well as tumor promoter gene (Menez et al, 2004).…”
Section: Lung Cancersupporting
confidence: 57%
“…Furthermore, after extraction of the primary tumor the cytotoxic T lymphocyte clone targeting mutated α-actinin 4 persisted many years in the patient's blood (Echchakir et al, 2001). In the subsequent study, it has been shown that the above point mutation removes antiproliferative effect of ACTN4 protein in the cancer cell line and supports the notion that ACTN4 may be both tumor suppressor as well as tumor promoter gene (Menez et al, 2004).…”
Section: Lung Cancersupporting
confidence: 57%
“…Although the precise roles of ␣-actinin 4 in tumorigenesis are controversial, ␣-actinin 4 has been proposed to play a role in cell motility and cancer invasion (4,(22)(23)(24)(25). Our findings that ␣-actinin 4 has a role in transcriptional regulation provides a possible, additional mechanism by which mutant ␣-actinin 4 might contribute to the pathogenesis of these diseases.…”
Section: Discussionmentioning
confidence: 61%
“…Loss of a-actinin-4 disrupts the integrity of tight junctions and has been associated with cancer invasion and metastasis (Nakatsuji et al, 2008). However, in most studies, high levels of a-actinin-4 correlate with poor outcome or advanced disease (Honda et al, 1998;Honda et al, 2005;Honda et al, 2004;Kikuchi et al, 2008;Menez et al, 2004;Patrie et al, 2002;Weins et al, 2007;Welsch et al, 2009;Yamada et al, 2010;Yamamoto et al, 2007;Yamamoto et al, 2009), and the relevance of its role in tight junction assembly for cancer thus remains unclear. Other functions of a-actinin-4, such as in leading edge protrusion (Honda et al, 1998) might contribute to metastasis and further study is warranted.…”
Section: Cortexmentioning
confidence: 99%
“…a-Actinin-4 is generally found at the leading edges of motile cells in lamellipodia. a-Actinin (especially a-actinin-4) is implicated in multiple tumours, including breast (Guvakova et al, 2002), ovarian (Yamamoto et al, 2009) (where it is a prognostic indicator of poor outcome), pancreas (Kikuchi et al, 2008) and lung cancers (Menez et al, 2004) (see Table 1). …”
Section: Stress Fibresmentioning
confidence: 99%
See 1 more Smart Citation